MIL-120(al) organic framework material and green synthesis method and application thereof
Patent Information
- Application Number
- CN202611145151.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]本发明的目的是提供一种MIL-120(Al)有机框架材料的绿色合成方法,以解决现有技术难以在室温、无加热、无高压条件下,以纯水为唯一助磨剂制备高结晶度MIL-120(Al)有机框架材料的技术问题
[0016]本发明的技术优点如下:本发明能够以水为唯一助磨剂,在常温常压下实现高结晶度MIL-120(Al)有机框架材料的制备;制备得到的MIL-120(Al)材料结晶度高,BET比表面积达500-650m2g-1,对二氧化碳的吸附量在25°C、1bar的条件下为3.5-4.0mmol
g-1,与水热法制备的MIL-120(Al)材料性能相当,且水热稳定性和循环稳定性优异。
Smart Images

Figure CN122917330A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of organic framework materials technology, specifically relating to a MIL-120(Al) organic framework material and its green synthesis method and applications. Background Technology
[0002] Post-combustion carbon capture is a key technology for addressing global climate change and controlling CO2 emissions. Traditional amine solution absorption methods suffer from high energy consumption (accounting for 60%-80% of total power plant energy consumption), severe equipment corrosion, and secondary pollution. Physically adsorbed metal-organic frameworks (MOFs), with their high specific surface area, tunable pore structure, and abundant surface functional groups, have become highly promising carbon capture adsorbents.
[0003] MIL-120(Al) is an aluminum-based microporous MOF composed of edge-shared Al(OH)4O2 octahedral infinite chains linked to pyromellitic acid (BTeC) ligands. It possesses a high density of μ2-OH groups and stacked aromatic ring adsorption sites, achieving a CO2 adsorption capacity of approximately 3.5 mmol at 25°C and 1 bar. g -1 Furthermore, it exhibits excellent hydrothermal stability (no performance loss after 10 days of boiling water reflux) and a regeneration energy consumption of only 44 kJ. mol -1 Its temperature is much lower than that of amine solutions, making it one of the few MOF materials that meet the core requirements for industrial carbon capture.
[0004] The core bottleneck currently hindering the large-scale production of MIL-120 (Al) lies in the synthesis process: existing mainstream preparation routes all rely on long-term high-temperature heating systems, which not only result in lengthy reaction cycles and low space-time yields, but also lead to the discharge of large amounts of process wastewater. Furthermore, the need for high-pressure and constant-temperature equipment significantly increases plant construction investment and production safety management costs, making it difficult to meet the demands of large-scale continuous production. Changing the preparation method often results in inherent defects in the MIL-120 (Al) product, such as insufficient crystallinity, a high proportion of amorphous impurities, and decreased gas adsorption performance. Summary of the Invention
[0005] The purpose of this invention is to provide a green synthesis method for MIL-120(Al) organic framework materials, in order to solve the technical problem that it is difficult to prepare highly crystalline MIL-120(Al) organic framework materials using pure water as the sole grinding aid under room temperature, no heating, and no high pressure conditions in the prior art.
[0006] The green synthesis method for the MIL-120(Al) organic framework material includes the following steps: Step 1, Raw material mixing: Mix the aluminum source and pyromellitic acid evenly, add deionized water as a grinding aid, and mix to obtain a mixture. Step 2, ball milling reaction: Place the mixture in a ball mill and ball mill it at room temperature and pressure to obtain a crude product; Step 3, Post-processing: Wash the crude product with deionized water until the filtrate is neutral, filter and dry to obtain powder; Step 4, Activation: The dried powder is heated and degassed to achieve activation, resulting in activated MIL-120(Al) organic framework material.
[0007] Preferably, in step 1, the aluminum source is one or a mixture of aluminum glycolate, sodium aluminate, aluminum nitrate nonahydrate, and aluminum hydroxide.
[0008] Preferably, in step 1, the aluminum source is sodium aluminate, and acetic acid is also added to the mixture as a pH adjuster to adjust the pH of the mixture to 3-4.
[0009] Preferably, in step 1, the aluminum source and pyromellitic acid are mixed in a molar ratio of 2-8:1 as raw materials.
[0010] Preferably, in step 1, the amount of deionized water added is 20%-300% of the total mass of the raw materials.
[0011] Preferably, in step 2, the ball-to-material mass ratio in the ball mill is 5-30:1, the ball mill speed is 200-600 rpm, and the ball milling reaction time is 1-4 hours.
[0012] Preferably, in step 3, the crude product is dispersed in 10-20 times its own weight of deionized water and washed 2-3 times at room temperature.
[0013] Preferably, in step 4, the activation heating temperature is 50-150℃ and the degassing vacuum degree is ≤10. -5 mbar, degassing time is 4-8 hours.
[0014] The present invention also provides a MIL-120(Al) organic framework material, which is prepared by the above method.
[0015] The present invention also provides an application of the MIL-120(Al) organic framework material as described above in the adsorption and separation of CO2.
[0016] The technical advantages of this invention are as follows: This invention enables the preparation of highly crystalline MIL-120(Al) organic framework materials using water as the sole grinding aid at room temperature and pressure; the prepared MIL-120(Al) material exhibits high crystallinity and a BET specific surface area of 500-650 m². 2 g -1The adsorption capacity for carbon dioxide at 25°C and 1 bar was 3.5-4.0 mmol. g -1 Its performance is comparable to that of MIL-120(Al) material prepared by hydrothermal method, and it has excellent hydrothermal stability and cycling stability.
[0017] After process improvement, compared with the existing MIL-120(Al) organic framework material process, the reaction time is shortened from 24-72 hours in the traditional hydrothermal method to 1-4 hours, and the space-time yield is increased by more than 10 times, enabling continuous industrial production. The process does not use any organic solvents, using only deionized water as the sole grinding aid, and the solvent consumption is reduced by more than 90% compared to the hydrothermal method, significantly reducing wastewater treatment costs and meeting clean production requirements. Furthermore, this invention conducts the reaction entirely at room temperature, eliminating the need for high-pressure reactors and any heating and temperature control equipment, greatly reducing equipment investment and operational complexity, and eliminating the safety risks associated with high temperature and high pressure. Attached Figure Description
[0018] Figure 1 The images show the XRD patterns of the products prepared in the various embodiments of the present invention and Comparative Examples 1 and 2.
[0019] Figure 2 This is the adsorption isotherm diagram of the product of Example 1 of the present invention measured at 25°C.
[0020] Figure 3 This is the adsorption isotherm diagram of the product of Example 2 of the present invention measured at 25°C.
[0021] Figure 4 This is the adsorption isotherm diagram of the product of Example 3 of the present invention measured at 25°C.
[0022] Figure 5 This is the adsorption isotherm diagram of the product of Example 4 of the present invention measured at 25°C.
[0023] Figure 6 This is the adsorption isotherm diagram of the product of Comparative Example 1 of the present invention measured at 25°C.
[0024] Figure 7 This is the adsorption isotherm diagram of the product of Comparative Example 2 of the present invention measured at 25°C. Detailed Implementation
[0025] The following detailed description of the embodiments, with reference to the accompanying drawings, will further illustrate the specific implementation of the present invention, in order to help those skilled in the art to have a more complete, accurate, and in-depth understanding of the inventive concept and technical solution of the present invention.
[0026] This invention provides a green synthesis method for MIL-120(Al) organic framework material, comprising the following steps: Step 1: Raw material mixing: Mix the aluminum source and pyromellitic ester (BTeC) evenly, add deionized water as a grinding aid, and mix to obtain a mixture.
[0027] In this step, aluminum source and pyromellitic acid (BTeC) are mixed at a molar ratio of 2-8:1 as raw materials. Deionized water is the only grinding aid. The amount of deionized water added is 20%-300% of the total mass of the raw materials, preferably 40%-200% of the total mass of the raw materials.
[0028] The aluminum source is selected from aluminum glycolate (Al(OH)(OAc)2). The mixture comprises one or more of the following: xH2O), sodium aluminate (NaAlO2), aluminum nitrate nonahydrate, and aluminum hydroxide; preferably: aluminum glycolate or sodium aluminate.
[0029] When the aluminum source is sodium aluminate, acetic acid needs to be added to the mixture in step 1 as a pH adjuster to adjust the pH of the reaction system (i.e., the mixture) to 3-4.
[0030] Step 2, ball milling reaction: Place the mixture in a ball mill and ball mill it at room temperature and pressure to obtain the crude product.
[0031] In this step, the ball-to-material mass ratio in the ball mill is 5-30:1, the ball mill speed is 200-600 rpm, and the ball milling reaction time is 1-4 hours. Preferably, the ball-to-material mass ratio is 10-20:1, the ball mill speed is 400 rpm, and the ball milling reaction time is 2-3 hours.
[0032] The ball mill is a planetary ball mill, a stirred ball mill, or a drum ball mill; the grinding media in the ball mill are stainless steel balls, zirconia balls, or agate balls.
[0033] Step 3, Post-processing: Wash the crude product with deionized water until the filtrate is neutral, filter and dry to obtain MIL-120(Al) material powder.
[0034] In this step, the crude product is dispersed in 10-20 times its own weight of deionized water and washed 2-3 times at room temperature. The washing method at room temperature is any one or any combination of stirring washing, centrifugal washing, and vacuum filtration washing.
[0035] Step 4, Activation: The dried powder is heated and degassed to achieve activation, resulting in activated MIL-120(Al) organic framework material.
[0036] In this step, the activation heating temperature is 50-150℃, and the degassing vacuum degree is ≤10. -5 mbar, degassing time is 4-8 hours.
[0037] The present invention also provides a MIL-120(Al) organic framework material, which is prepared by the above method.
[0038] Testing revealed that the BET specific surface area of the MIL-120(Al) organic framework material obtained by the aforementioned green synthesis method was 500-650 m². 2 g -1 The MIL-120(Al) organic framework material was applied to CO2 adsorption. Tests showed that, at 25°C and 1 bar, the CO2 adsorption capacity was 3.5-4.0 mmol. g -1 Dynamic adsorption of a mixed gas (20% CO2 / N2 (V / V, i.e., a mixture of 20% CO2 and 80% N2 by volume) was performed at 25°C and atmospheric pressure, and the adsorption capacity for CO2 was 1.7-2.2 mmol. g -1 The corresponding CO2 / N2 separation coefficient is above 30.
[0039] The present invention also provides an application of the MIL-120(Al) organic framework material as described above in the adsorption and separation of CO2. For example, the MIL-120(Al) organic framework material is applied to the adsorption and separation of CO2 in post-combustion flue gas.
[0040] Using the green synthesis method of this invention, high-purity MIL-120(Al) organic framework material can be obtained simply by water washing at room temperature, without the need for complex purification steps. The prepared MIL-120(Al) material has high crystallinity, with performance comparable to samples prepared by hydrothermal methods, and exhibits excellent hydrothermal and cycling stability. The reaction time is reduced from 24-72 hours in the traditional hydrothermal method to 1-4 hours, a reduction of more than 80%, and the space-time yield is increased by more than 10 times, enabling continuous industrial production.
[0041] The aforementioned green synthesis method uses no organic solvents whatsoever, employing only deionized water as the sole grinding aid, and generates no organic wastewater discharge. Solvent usage is reduced by over 90% compared to the hydrothermal method, significantly lowering wastewater treatment costs and meeting clean production requirements. Raw materials are inexpensive and readily available, the process is simple and controllable, enabling kilogram-level batch production, and production costs are reduced by over 40% compared to the hydrothermal method.
[0042] The entire preparation process takes place at room temperature, eliminating the need for a high-pressure reactor or any heating and temperature control equipment. This significantly reduces equipment investment and operational complexity, and eliminates the safety risks associated with high temperature and pressure. Furthermore, the process does not involve heating or high-pressure energy consumption, requiring only the ball mill's electrical energy, resulting in a total energy consumption reduction of over 70% compared to traditional hydrothermal methods. Simultaneously, the dosage of grinding aids and the ball-to-material ratio have a very wide range of applicability, allowing for flexible adjustments based on different production scales and equipment conditions, facilitating industrial scaling-up.
[0043] The present invention will be further described in detail below through specific embodiments: Example 1 This embodiment provides a green synthesis method for MIL-120(Al) organic framework material, including the following steps: Step 1: Mixing raw materials: Weigh 80 mmol of aluminum glycolate (Al(OH)(OAc)2) Weigh out 15g of 1.38H2O; weigh out 20mmol of pyromellitic tetracarboxylic acid (BTeC), weighing 5.08g. Place both in an agate mortar and mix thoroughly as raw material. Add 8g of deionized water as the sole grinding aid to the raw material, with the deionized water accounting for approximately 40% of the total mass of the raw material. Mix thoroughly to obtain a mixture.
[0044] Step 2, ball milling reaction: Transfer the mixture to the stainless steel ball mill jar of a 500mL planetary ball mill, add 400g of stainless steel balls as the ball milling medium, with a ball-to-material mass ratio of 20:1, and ball mill the mixture at 400rpm for 2.5 hours at room temperature to obtain a white crude product.
[0045] Step 3, Post-processing: The crude product was dispersed in 400 mL of deionized water and washed three times at room temperature by stirring and centrifugation to obtain a clean solid product. The solid product was dried in air at 80°C for 10 hours to obtain MIL-120(Al) material powder. The yield of MIL-120(Al) material obtained in this step was 78%.
[0046] Step 4, Activation: The dried powder is activated at 150℃ and a vacuum degree of 10. -6 Degassing at mbar for 6 hours yielded activated MIL-120(Al) organic framework material.
[0047] Example 2 This embodiment provides a green synthesis method for MIL-120(Al) organic framework material, including the following steps: Step 1: Mixing raw materials: Weigh 80 mmol of aluminum glycolate (Al(OH)(OAc)2) Weigh out 15g of 1.38H2O; weigh out 20mmol of pyromellitic tetracarboxylic acid (BTeC), weighing 5.08g. Place both in an agate mortar and mix thoroughly as raw material. Add 40g of deionized water as the sole grinding aid to the raw material, with the deionized water accounting for approximately 200% of the total mass of the raw material. Mix thoroughly to obtain a mixture.
[0048] Step 2, ball milling reaction: Transfer the mixture to the stainless steel ball mill jar of a 500mL planetary ball mill, add 200g of stainless steel balls as the ball milling medium, with a ball-to-material mass ratio of 10:1, and ball mill the mixture at 400rpm for 3 hours at room temperature to obtain a white crude product.
[0049] Step 3, Post-processing: The crude product was dispersed in 400 mL of deionized water and washed three times at room temperature by stirring and centrifugation to obtain a clean solid product. The solid product was dried in air at 80°C for 10 hours to obtain MIL-120(Al) material powder. The yield of MIL-120(Al) material obtained in this step was 75%.
[0050] Step 4, Activation: The dried powder is activated at 150℃ and a vacuum degree of 10. -6 Degassing at mbar for 6 hours yielded activated MIL-120(Al) organic framework material.
[0051] Example 3 This embodiment provides a green synthesis method for MIL-120(Al) organic framework material, including the following steps: Step 1: Raw material mixing: Weigh 640 mmol sodium aluminate (NaAlO2), mass 52.48 g; weigh 160 mmol pyromellitic acid (BTeC), mass 40.64 g. Mix the two in a stainless steel mortar until homogeneous, as the raw material. Add 46 g of deionized water as the sole grinding aid to the raw material, the deionized water accounting for approximately 50% of the total mass of the raw material. Mix thoroughly, then slowly add acetic acid dropwise to the mixture to adjust the pH of the system to approximately 3.5, obtaining the final mixture.
[0052] Step 2, ball milling reaction: The mixture was evenly dispersed and transferred to four 500mL planetary ball mill jars. 1.8kg of stainless steel balls were added as the ball milling medium, with a ball-to-material mass ratio of 20:1. The mixture was ball milled at 350rpm for 3 hours at room temperature to obtain a white crude product.
[0053] Step 3, Post-processing: The crude product was dispersed in 1.6 L of deionized water and washed three times by centrifugation at room temperature to obtain a filter cake. The filter cake was dried in air at 80 °C for 12 hours to obtain MIL-120(Al) material powder. The yield of MIL-120(Al) material obtained in this step was 82%.
[0054] Step 4, Activation: The dried powder is activated at 120°C and a vacuum degree of 10. -6 Degassing at mbar for 8 hours yielded activated MIL-120(Al) organic framework material.
[0055] Example 4 This embodiment provides a green synthesis method for MIL-120(Al) organic framework material, including the following steps: Step 1, Raw material mixing: Weigh 4.79 mol of aluminum glycolate (Al(OH)(OAc)2) Weigh out 1.38H2O (885g); weigh out 1.19mol of pyromellitic tetracarboxylic acid (BTeC), 303g. Place both in a twin-screw mixer and mix thoroughly to obtain the raw material. Add 840g of deionized water as the sole grinding aid to the raw material, approximately 50% of the total raw material mass, and mix thoroughly to obtain the mixture.
[0056] Step 2, ball milling reaction: The mixture was continuously added to a 20L horizontal drum ball mill, and 17.8kg of zirconia balls were added as the ball milling medium. The ball-to-material mass ratio was 15:1. The mixture was ball milled at 300rpm for 3.5 hours at room temperature to obtain a white crude product.
[0057] Step 3, Post-processing: The crude product was transferred to a stirred tank, 15L of deionized water was added, and the mixture was centrifuged and washed three times at room temperature to obtain a filter cake. The filter cake was dried at 90℃ for 12 hours to obtain 890g of MIL-120(Al) powder. The yield of the MIL-120(Al) material obtained in this step was 76%.
[0058] Step 4, Activation: The dried powder is compressed into tablets and then passed through a 40-60 mesh sieve to obtain 40-60 mesh particles; the particles are then packed into an adsorption column with a diameter of 0.8 cm and activated at 150°C and a vacuum degree of 10. -6 Degassing at mbar for 4 hours yielded activated MIL-120(Al) organic framework material.
[0059] To verify the technical effects of the present invention, the following comparative examples were also provided: Comparative Example 1 In this comparative example, MIL-120(Al) organic framework material was prepared according to the existing hydrothermal method. The steps are as follows: 1 mmol BTeC, 8 mmol NaOH, and 4 mmol aluminum nitrate nonahydrate were dissolved in 10 mL of deionized water and then transferred to a 23 mL polytetrafluoroethylene reactor. The reactor was subjected to high pressure reaction at 180 °C for 24 hours. Afterward, the product was obtained by centrifugation, washing, and drying.
[0060] Comparative Example 2 This comparative example provides a method for synthesizing MIL-120(Al) organic framework material, the steps of which are as follows: Step 1: Mixing raw materials: Weigh 80 mmol of aluminum glycolate (Al(OH)(OAc)2) Weigh out 15g of 1.38H2O; weigh out 20mmol of pyromellitic tetracarboxylic acid (BTeC), weighing 5.08g. Place both in an agate mortar and mix thoroughly as raw material. Add 2g of deionized water as the sole grinding aid to the raw material, with the deionized water accounting for approximately 10% of the total mass of the raw material. Mix thoroughly to obtain a mixture.
[0061] Step 2, ball milling reaction: Transfer the mixture to the stainless steel ball mill jar of a 500mL planetary ball mill, add 400g of stainless steel balls as the ball milling medium, with a ball-to-material mass ratio of 20:1, and ball mill the mixture at 400rpm for 2.5 hours at room temperature to obtain a white crude product.
[0062] Step 3, Post-processing: The crude product was dispersed in 400 mL of deionized water and washed three times at room temperature using a combination of stirring and centrifugation to obtain a clean solid product. The solid product was then dried in air at 80°C for 10 hours to obtain MIL-120(Al) material powder. The yield of the solid material obtained in this step was 78%.
[0063] Step 4, Activation: The dried powder is activated at 150℃ and a vacuum degree of 10. -6 Degassing at mbar for 6 hours yielded the activated product.
[0064] The difference between this comparative example and Example 1 is that the amount of deionized water added as a grinding aid is significantly reduced.
[0065] Comparative Example 3 This comparative example provides a method for synthesizing MIL-120(Al) organic framework material, the steps of which are as follows: Step 1: Raw material mixing: Weigh 640 mmol sodium aluminate (NaAlO2), mass 52.48 g; weigh 160 mmol pyromellitic acid (BTeC), mass 40.64 g. Place both in a stainless steel mortar and mix thoroughly to obtain the raw material. Add 46 g of deionized water as the sole grinding aid to the raw material, the deionized water accounting for approximately 50% of the total mass of the raw material. Mix thoroughly to obtain the mixture.
[0066] Step 2, ball milling reaction: The mixture was evenly dispersed and transferred to four 500mL planetary ball mill jars. 1.8kg of stainless steel balls were added as the ball milling medium, with a ball-to-material mass ratio of 20:1. The mixture was ball milled at 350rpm for 3 hours at room temperature to obtain a white crude product.
[0067] Step 3, Post-processing: The crude product was dispersed in 1.6 L of deionized water and washed three times by centrifugation at room temperature to obtain a filter cake. The filter cake was dried in air at 80 °C for 12 hours to obtain MIL-120(Al) material powder. The yield of the solid material obtained in this step was 82%.
[0068] Step 4, Activation: The dried powder is activated at 120°C and a vacuum degree of 10. -6 Degassing at mbar for 8 hours yielded the activated product.
[0069] The difference between this comparative example and Example 1 is that no pH adjuster was added when the aluminum source was sodium aluminate.
[0070] Comparative Example 4 This comparative example provides a method for synthesizing MIL-120(Al) organic framework material, the steps of which are as follows: Step 1: Raw material mixing: Weigh 640 mmol sodium aluminate (NaAlO2), mass 52.48 g; weigh 160 mmol pyromellitic acid (BTeC), mass 40.64 g. Mix the two in a stainless steel mortar until homogeneous, as the raw material. Add 46 g of deionized water as the sole grinding aid to the raw material, the deionized water accounting for approximately 50% of the total mass of the raw material. Mix thoroughly, then slowly add acetic acid dropwise to the mixture to adjust the pH of the system to approximately 6, obtaining the final mixture.
[0071] Step 2, ball milling reaction: The mixture was evenly dispersed and transferred to four 500mL planetary ball mill jars. 1.8kg of stainless steel balls were added as the ball milling medium, with a ball-to-material mass ratio of 20:1. The mixture was ball milled at 350rpm for 3 hours at room temperature to obtain a white crude product.
[0072] Step 3, Post-processing: The crude product was dispersed in 1.6 L of deionized water and washed three times by centrifugation at room temperature to obtain a filter cake. The filter cake was dried in air at 80 °C for 12 hours to obtain MIL-120(Al) material powder. The yield of the solid material obtained in this step was 82%.
[0073] Step 4, Activation: The dried powder is activated at 120°C and a vacuum degree of 10. -6 Degassing at mbar for 8 hours yielded the activated product.
[0074] The products obtained in Examples 1-4 and Comparative Examples 1-4 were used as samples for testing. All of these samples were applied to CO2 adsorption, and the adsorption capacity of CO2 and the CO2 / N2 separation coefficient were tested under the conditions of 25°C and 1 bar. The results are shown in Table 1.
[0075] Table 1 Performance indicators of the products obtained in Examples 1-4 and Comparative Examples 1-4
[0076] The table above covers: Adsorption isotherm test: The adsorbent is activated according to the activation conditions in the specific case; the N2 adsorption isotherm is measured at -196℃ (liquid nitrogen bath) to calculate the specific surface area; the CO2 adsorption isotherm is measured at 25℃ (constant temperature water bath) to obtain the CO2 adsorption capacity at 25°C 1 bar.
[0077] Dynamic adsorption test: The adsorbent was activated according to the activation conditions in the specific case. After cooling to 25℃, 20% CO2 / N2 (V / V) was introduced at atmospheric pressure, and the CO2 adsorption capacity and CO2 / N2 separation coefficient were obtained from the breakthrough curve.
[0078] The XRD patterns of the products prepared in each embodiment and Comparative Examples 1 and 2 are shown below. Figure 1 As shown, the adsorption isotherm tests of each embodiment and Comparative Examples 1 to 2 are as follows. Figures 2-7 As shown in the figure, the CO2 adsorption isotherm was measured at 25°C (constant temperature water bath), thus obtaining the CO2 adsorption amount under the conditions of 25°C and 1 bar.
[0079] By analyzing the data in the table above and the appendix... Figures 1-7 The comparison shows that: Comparative Example 1: The crystallinity is better than that of the product of this invention, but the specific surface area is slightly smaller. The CO2 adsorption capacity at 1 bar, the dynamic CO2 adsorption capacity at 20% CO2 / N2 (V / V), and the CO2 / N2 separation coefficient obtained by testing at 25°C are similar to those of this invention. However, this invention has a shorter reaction time, less solvent consumption, and does not require high-temperature and high-pressure equipment, yet it can achieve the same carbon dioxide adsorption effect. Comparative Example 2: Except for the addition of 10% deionized water as a grinding aid, the remaining steps were the same as in Example 1. Its XRD pattern showed weaker peak intensity and impurities, indicating that the crystallinity of the product was lower than that of the product of this invention and that it contained impurities. The tested CO2 adsorption capacity at 1 bar, the dynamic CO2 adsorption capacity at 20% CO2 / N2 (V / V), and the CO2 / N2 separation coefficient at 25°C were all lower than those of this invention. This demonstrates that an appropriate amount of deionized water as a grinding aid is crucial for the ball milling process. Reason: In Comparative Example 2, with the addition of 10% deionized water, there was a lack of sufficient liquid-phase mass transfer medium and crystallization guidance during ball milling, making it difficult for the ligands and aluminum source to effectively coordinate and bond, resulting in a product dominated by low crystallinity and impurities. In this invention, the addition of deionized water relies on the formation of an interfacial liquid film to promote ion mass transfer and regulate the orderly growth of crystals, which is a necessary condition for obtaining a highly crystalline pure phase MIL-120 (Al) through room temperature ball milling.
[0080] Comparative Examples 3 and 4: In Comparative Example 3, acetic acid was not added to adjust the pH; the remaining steps were the same as in Example 3. In Comparative Example 4, acetic acid was added to adjust the pH to 6; the remaining steps were the same as in Example 3. At 25°C, the CO2 adsorption capacity at 1 bar was only 0.21 and 0.5 mmol / g, respectively, far lower than the well-crystallized MIL-120 in Examples 1-4, indicating that pH adjustment is crucial for the preparation of MIL-120(Al). This group of comparative experiments used a MIL-120(Al) synthesis system without pH adjustment; the remaining synthesis process parameters were consistent with those in Example 3 of this invention. This single variable was used to investigate the effect of pH on the preparation of the target material and CO2 adsorption performance. From the perspective of the synthesis mechanism, pH directly determines the degree of deprotonation of organic ligands, which in turn affects the coordination mode between ligands and metal ions, ultimately leading to the formation of different crystal structures. The crystal growth of MIL-120(Al) and the coordination reaction between ligands and aluminum sources are highly sensitive to the acid-base environment of the system. In the original reaction system without pH adjustment, the acid-base environment of the solution is unbalanced, which cannot provide suitable conditions for the formation of MIL-120 (Al) crystals. The present invention has been described above by way of example with reference to the accompanying drawings. Obviously, the specific implementation of the present invention is not limited to the above-described manner. Any non-substantial improvements made using the inventive concept and technical solution of the present invention, or the direct application of the inventive concept and technical solution of the present invention to other occasions without modification, are all within the protection scope of the present invention.
Claims
1. A green synthesis method for MIL-120(Al) organic framework material, characterized in that, Includes the following steps: Step 1, Raw material mixing: Mix the aluminum source and pyromellitic acid evenly, add deionized water as a grinding aid, and mix to obtain a mixture. Step 2, ball milling reaction: Place the mixture in a ball mill and ball mill it at room temperature and pressure to obtain a crude product; Step 3, Post-processing: Wash the crude product with deionized water until the filtrate is neutral, filter and dry to obtain powder; Step 4, Activation: The dried powder is heated and degassed to achieve activation, resulting in activated MIL-120(Al) organic framework material.
2. The green synthesis method of MIL-120(Al) organic framework material according to claim 1, characterized in that, In step 1, the aluminum source is one or a mixture of aluminum glycolate, sodium aluminate, aluminum nitrate nonahydrate, and aluminum hydroxide.
3. The green synthesis method of MIL-120(Al) organic framework material according to claim 1, characterized in that, In step 1, the aluminum source is sodium aluminate. In step 1, acetic acid is also added to the mixture as a pH adjuster to adjust the pH of the mixture to 3-4.
4. The green synthesis method of MIL-120(Al) organic framework material according to claim 1, characterized in that, In step 1, aluminum source and pyromellitic acid are mixed at a molar ratio of 2-8:1 as raw materials.
5. The green synthesis method of MIL-120(Al) organic framework material according to claim 1, characterized in that, In step 1, the amount of deionized water added is 20%-300% of the total mass of the raw materials.
6. The green synthesis method of MIL-120(Al) organic framework material according to claim 1, characterized in that, In step 2, the ball-to-material mass ratio in the ball mill is 5-30:1, the ball mill speed is 200-600 rpm, and the ball milling reaction time is 1-4 hours.
7. The green synthesis method of MIL-120(Al) organic framework material according to claim 1, characterized in that, In step 3, the crude product is dispersed in 10-20 times its own weight of deionized water and washed 2-3 times at room temperature.
8. The green synthesis method of MIL-120(Al) organic framework material according to claim 1, characterized in that, In step 4, the activation heating temperature is 50-150℃, and the degassing vacuum degree is ≤10. -5 mbar, degassing time is 4-8 hours.
9. A MIL-120(Al) organic framework material, characterized in that: Prepared by the method described in any one of claims 1-8.
10. An application of the MIL-120(Al) organic framework material as described in claim 9 in the adsorption and separation of CO2.